(untitled) (Studia Prawnicze / The Legal Studies, 2009)
Obowiązująca obecnie Konstytucja stanowi w art. 9, że Rzeczpospolita Polska przestrzega wiążącego ją prawa międzynarodowego. Przepis ten nakłada na wszystkie organy władzy publicznej w Polsce obowiązek zapewnienia skuteczności umowom międzynarodowym, którymi Polska jest związana. Warunkiem wejścia aktów normatywnych jest ich ogłoszenie. Zasada ta odnosi się do wszystkich rodzajów aktów normatywnych, bo jak zauważył już Św. Tomasz, norma jedynie pomyślana, anieuzewnętrzniona przez prawodawcę, nie może być wiążącym wzorcem postępowania dla kogokolwiek poza samym prawodawcą. W Konstytucji zasada ta została wyrażona w art. 88 wprost jedynie do ustaw, rozporządzeń i aktów prawa miejscowego. Stosownie do art. 91 Konstytucji ratyfikowana umowa międzynarodowa stanowa część krajowego porządku prawnego i jest bezpośrednio stosowalna (chyba że jej stosowalnie jest uzależnione od wydania ustawy) dopiero po jej ogłoszeniu w Dzienniku Ustaw Rzeczypospolitej Polskiej. Article 9 of the Polish Constitution states: The Republic of Poland shall respect international law binding upon it. According to this provision all organs of public authority are obliged to ensure effectiveness of international agreements which are binding on Poland. The condition for direct effectiveness of international agreements in the national law (understood as a possibility of derivations rights and obligations for individuals from that agreements) is the official publication of the said conventions. This article analyses the provisions of Polish law governing the official publication of international agreements and assesses the long established practices in this area. As a result of this research several sensitive areas have been identified. First and foremost concerning the actual publication of concluded international agreements. Comparison of the number of international agreements concluded in years 2000-2008 available in the database of Polish Ministry of Foreign Affairs with the number of international agreements announced in the Official Journal shows that only 57% of those agreements were properly published. Furthermore problems have also been identified as: - failure to publish information on entry into force and the changes pertaining to the actual number of contracting parties, - failure to publish information about the deposit of the ratifying documents or documents terminating the agreement, - lack of or incomplete information about reservations or objections to the agreements submitted by the contracting parties, which makes it difficult or even impossible to establish the exact scope of the agreement, - delays in official publishing of international agreements (very often documents are published many years after the ratification or even after coming into force). Each of the above mentioned deficiencies concerning the proper official publication of international agreements is not acceptable in the democratic state governed by the rule of law, respecting the binding rules of international law. The authors propose an amendment of the existing legal rules and practice. In conclusion certain proposals de lege ferenda and proposals in relation to existing practices aiming towards eliminating irregularities in the official publication of international agreements in Poland are formulated.